Analyzing the relationship between air transportation and economic activities in East Asia & Pacific Region - Ao, Xiao Ling (2017)
The usage of air transportation and the activities of economic are interdependent. The reason for this conclusion is because the usage of air transportation provides employment and makes enables for certain economic activities, in return, the activities of economic stimulates the demand of air transportation’s usage. In other word, economic activities acting as a catalyst which driving air transportation’s demand, therefore, there is an interaction relationship between air transportation and economic activities. The main objective for this project is to study the relationship between air transportation and economic activities and to understand how these two factors have been interacted to each other in the period of 1990 - 2015 for the East Asia & Pacific Region. This project has been conducted through, (1) literature review for previous relative research studies in both economic activities and air transportation field. (2) Analyzing through different kinds of trend model which enable author to make a description of the relationship between GDP and Air Passenger Volume (APV) in the East Asia & Pacific Region (EAPR). (3) Identifying factors which making high, average or low impact on air transportation’s usage based on country level analysis, such as the demand for air passenger travel, supplies of the domestic market and international employment. (4) Furthermore, China-Yunnan, Brunei and Mongolia, total three case studies have been performed. In further detail, there are following three main procedures have been carried out for period 1990-2015, firstly, exploring the East Asia & Pacific Region’s variable growth trend for both GDP and APV. Finding out the best fit trend model for the East Asia & Pacific Region’s analysis. Secondly, studying the best fit trend for interaction behaviors between GDP and APV for total 20 individual countries and regions. Understanding interaction impact factors such as income categories and demographics. Thirdly, case studies for individual countries have been employed with each representative based on the rate of impact from economic on air transportation. Therefore, the three steps of analyzing have developed a model under an interactive pattern which could describe the relationship between economic activities and air transportation.